Critical education (Institute for Critical Education Studies, 2010)
"Critical Education is an international peer-reviewed journal, which seeks manuscripts that critically examine contemporary education contexts and practices. Critical Education is interested in theoretical and empirical research as well as articles that advance educational practices that challenge the existing state of affairs in society, schools, and informal education."